Dehydroepiandrosterone suppresses human colorectal cancer progression through ER stress-mediated autophagy and apoptosis in a p53-independent manner - Nguyen, Thi-Huong; Ko, Huey-Jiun; Tsai, Po-Yu; Cheng, Tai-Shan; Tran, Thu-Ha; Doan, Ly Hien; Hsiao, Michael; Chang, Peter Mu-Hsin; Liu, Hsiao-Sheng; Hong, Yi-Ren; Huang, Chi-Ying F. (Frontiers in Pharmacology, 2024)
Colorectal cancer (CRC) is one of the primary contributors to cancer-related fatalities, with up to 80% of advanced CRC cases exhibiting mutations in the p53 gene.Unfortunately, the development of new compounds targeting mutant p53 is quite limited. The anticancer effects of Dehydroepiandrosterone (DHEA) on various cancers have been reported. However, the suppressive effect of DHEA on CRC cells harboring wild-type or mutant p53 gene remains controversial. This study emphasized revealing the suppressive mechanism and the effect of DHEA on CRC cell tumorigenesis in the presence of wild-type or mutant p53 gene. We demonstrate that DHEA causes CRC cell death and cell cycle arrest in a dose and time-dependent manner. Notably, DHEA exhibits similar inhibitory effects on CRC cells regardless of the p53 gene status.Further study reveals that DHEA induces endoplasmic reticulum (ER) stress and triggers PERK/eIF2/ATF4/CHOP UPR signaling pathway to activate autophagy followed by apoptosis, which was confirmed by suppression of 4-phenylbutyric acid (an ER stress inhibitor) or knockdown either ATF4 or CHOP. DHEA-induced apoptosis was attenuated by silencing ATG5 gene in either p53 +/+ or p53 -/-CRC cells, indicating autophagy regulation of apoptosis. Furthermore, DHEA treatment accompanied by bafilomycin A1 (a blocker of autophagosome degradation) leads to the accumulation of ATF4, CHOP, DR5, and p21 levels in CRC cells, implying that the degradative autophagy machinery regulates these four molecules. Consistently, DHEA demonstrates its inhibitory effect by suppressing CRC tumor formation in vivo.Altogether, we provide compelling evidence that DHEA is a potential therapeutic candidate for CRC patient treatment regardless of the p53 status through ER stress-PERK-autophagy-apoptosis axis.